Studies on the Decay of Bamboo (Dendrocalamus strictus) during Outside Storage-degradation of Lignin - Chandra, A.; Guha, S. R. D. (Indian Forester, 1981)
During outside storage the bamboos (D. strictus) were attacked by various wood destroying microorganisms. The studies showed that like other major constituents lignin also progressively decreased due to decay as the storage period increased. This type of simultaneous depletion of the major constituents in wood bamboo is caused due to white rot type of fungal decay. The studies also showed that lignin macromolecule had chemically changed. The elemental analysis of the dioxane lignin isolated from fresh and stored (decayed) bamboo as well as the emperical formula for an average C9 or phenylpropane unit indicates variation in the nature of two lignins. The decayed lignins were higher in oxygen,lower in hydrogen, methoxyl value and carbon contents than of the sound bamboo lignin. The alkaline nitrobenzene oxidation of the decayed bamboo lignins gave lower yields of the main product, viz vanillin, syriagaldehyde and p-hydroxy-benzalhyde. In addition the molar ratio of syringaldehyde to vanillins(S/V) also increased which suggest the preferential degradation of the guaicyl units of the lignin during decay. Ultra violet studies carried out on decayed bamboo lignins show greater absorptions at 260 nm and 300 nm indicating changes in the lignin macromolecule.